2023
DOI: 10.1001/jama.2023.0550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Argatroban Plus Intravenous Alteplase vs Intravenous Alteplase Alone on Neurologic Function in Patients With Acute Ischemic Stroke

Abstract: ImportancePrevious studies suggested a benefit of argatroban plus alteplase (recombinant tissue-type plasminogen activator) in patients with acute ischemic stroke (AIS). However, robust evidence in trials with large sample sizes is lacking.ObjectiveTo assess the efficacy of argatroban plus alteplase for AIS.Design, Setting, and ParticipantsThis multicenter, open-label, blinded end point randomized clinical trial including 808 patients with AIS was conducted at 50 hospitals in China with enrollment from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
8
28
0
Order By: Relevance
“…Due to the excessive hemorrhage transformation rates associated with conventional anticoagulants, most efforts to reduce END have focused on novel anticoagulants combined with antiplatelet therapies. No harmful profile of argatroban was observed even in patients who received intravenous alteplase, suggesting the possible safety of anticoagulants . In our study, a combined regimen of antiplatelet and argatroban in patients with END did not increase the risk of symptomatic intracerebral hemorrhage and severe systemic bleeding, which is in line with previous studies …”
Section: Discussionsupporting
confidence: 91%
“…Due to the excessive hemorrhage transformation rates associated with conventional anticoagulants, most efforts to reduce END have focused on novel anticoagulants combined with antiplatelet therapies. No harmful profile of argatroban was observed even in patients who received intravenous alteplase, suggesting the possible safety of anticoagulants . In our study, a combined regimen of antiplatelet and argatroban in patients with END did not increase the risk of symptomatic intracerebral hemorrhage and severe systemic bleeding, which is in line with previous studies …”
Section: Discussionsupporting
confidence: 91%
“…Previous studies on the use of argatroban in AIS used National Institutes of Health Stroke Scale (NIHSS) score [16,24]. To our knowledge, no correlation study has used MESSS score to evaluate the effect of argatroban in the treatment of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2018) [16] demonstrated that argatroban has no additional benefit on short-term outcomes compared to high-dose aspirin alone. A recent study reported that argatroban is safe but does not improve functional outcome at 90 days in Chinese patients with AIS treated with recombinant tissue-type plasminogen activator (r-tPA) [24]. A meta-analysis concluded that patients with AIS might not benefit from the combined therapy with argatroban [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, ARAMIS (Antiplatelet vs R-tPA for Acute Mild Ischemic Stroke) recently confirmed the findings of PRISMS, favoring dual antiplatelet therapy in a similar population. 14 ARAMIS showed that the same direction of effect favoring antiplatelet therapy using a modified Rankin scale, albeit nonsignificantly, reduces the likelihood that a more sensitive measure, such as cognition, would detect a treatment effect in the opposite direction. We are still determining whether patients at higher risk for disability or deterioration, such as those with LVO or perfusion deficits, would benefit from IVT.…”
Section: Treatment Eligibility: Beyond Timementioning
confidence: 99%